PRODUCT DEVELOPMENT STRATEGIES OF TRADITIONAL HANDICRAFTS OF SANJIANG DONG ETHNIC GROUP: A STUDY BASED ON CONSUMER PREFERENCES: PRODUCT DEVELOPMENT STRATEGIES OF TRADITIONAL HANDICRAFTS OF SANJIANG DONG ETHNIC GROUP: A STUDY BASED ON CONSUMER PREFERENCES - Liang Xianfei; Zairul Anuar Md. Dawam; Sim Chee Cheang (Jurnal Gendang Alam (GA), 2024)
ABSTRACT This study aims to explore consumer preferences for traditional handicrafts of the Dong ethnic group in Sanjiang and to provide a theoretical basis for new product development. Through interviews and thematic analyses of 40 consumers, the study provides an in-depth analysis of consumers’ demographic characteristics, market demand, and suggestions for improvement of existing products. The results show that consumers highly value the cultural significance and traditional craftsmanship of Dong handicrafts, but at the same time hope that the products can incorporate modern design elements to meet personalized needs. Based on the study’s results, this paper suggests that the cultural heritage of Dong handicrafts can be combined with economic benefits by enriching product variety, improving craftsmanship, optimizing branding, and developing products with high portability to meet consumer expectations and enhance market competitiveness. Keywords: Consumer preferences, traditional handicrafts, product development, thematic analysis, market